Preoperative Hypoalbuminemia as a Predictor of Postoperative Complications in Elective GI Surgery (The Planet, 2025)
Background: Serum albumin is a key biomarker that reflects the nutritional and inflammatory status of patients and plays a critical role in predicting surgical outcomes. Hypoalbuminemia, or low serum albumin levels, has been associated with increased risk of postoperative complications. This study aimed to assess preoperative hypoalbuminemia as a predictor of postoperative complications in elective GI surgery. Methods & Materials: This prospective observational study was conducted at Department of Surgery, Sir Salimullah Medical College and Mitford Hospital, Dhaka, from from July 2021to December 2021. A total of 38 patients were selected as study subjects by purposive sampling technique. Each group had 19 patients (Group A: Albumin level
Keywords: Hypoalbuminemia; Postoperative Complications; Elective GI Surgery; Wound Infection